The Development of Interactive Multimedia Based on TPACK to Enhance Students' Science Process Skills on Living Cell Matter - Sigit Subagja; Bibin Rubini; Surti Kurniasih (Jurnal Penelitian Pendidikan IPA, 2023)
This work aims to create interactive multimedia based on TPACK to enhance students' science process skills (SPS) on living cell matter. It offers an alternate method of learning that relies on creating and applying information technology to achieve learning goals (SPS). The ADDIE paradigm was utilized in the research and development process to create Interactive multimedia. These steps are Analysis, Design, Development, Implementation, and Evaluation. The Interactive Multimedia development product was determined to be possible to be incorporated into a learning product based on the research findings and several validation and implementation tests carried out during the development process. The Interactive Multimedia is practicable, as evidenced by the percentage of data collected from the validator and the outcomes of the implementation test to the pupils. The students' SPS N-Gain analysis results obtained a score of 0.78 in the high category. In other words, a product that has undergone testing and validation may be one that can be used to aid in learning about living cells and can enhance students' science process skills.